Post‐transplant biliary complications: An analysis from a predominantly living donor liver transplant center. Issue 6 (22nd May 2013) - Wadhawan, Manav; Kumar, Ajay; Gupta, Subash; Goyal, Neerav; Shandil, Rajeev; Taneja, Sunil; Sibal, Anupam
Abstract Background and Aim Biliary anastomosis is the Achilles' heel of liver transplant. The reported incidence of biliary complications is 5–15% after deceased donor liver transplantation, and 20–34% after right‐lobe live donor liver transplantation (LDLT). We report our experience from an LDLT program. Methods Between September 2006 and August 2010, 338 liver transplants were performed. Biliary reconstructions were done with an end‐to‐end choledochocholedochostomy in 307 cases. All recipients were monitored for any evidence of bile leak or stricture. Results Of 338 transplants performed during this time period, 65 patients had biliary complications (19%). Of these, 30 were biliary leaks, and 35 patients had biliary stricture. Four were cut surface leaks, which settled without any intervention. One patient had leak from primary hepaticojejunostomy, which settled on conservative management. Twenty‐five patients had anastomotic leaks, of which 17 underwent endoscopic retrograde cholangiopancreatography and stenting; another eight underwent re‐exploration and hepaticojejunostomy. Forty‐five patients had biliary strictures. Of these, 10 patients had bile leak initially, followed by biliary stricture. Patients with a double duct anastomosis had a significantly higher risk of developing biliary complications compared with those with a single duct anastomosis. There was no statistically significant difference in survival between those with or without biliary complications. Conclusions Biliary complications are common after LDLT. Most leaks will subsequently form strictures. Endoscopic retrograde cholangiopancreatography is the first‐line treatment for biliary complications, with surgery required in a minority of cases. The incidence of biliary complications is higher in multiple duct anastomoses. Biliary complications are not associated with increased mortality.